2015
DOI: 10.14267/cjssp.2015.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Holistic education – A sustainable model for the future

Abstract: The role of higher education and of universities stands at a critical position in the twenty first century. There exists a need to identify a sustainable paradigm for higher education and the existential role of universities. Additionally, the concept of the 'third mission' is becoming an important indicator across Europe for measuring the success of universities. The need to identify the existential role of universities and the need for a sustainable model of higher education and incorporation of the third mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Holistic education is based on experiential learning methods, and students are defined as active participants in the educational process, building their knowledge through experience [4,9,13,[55][56][57]. However, this study found that students have difficulty changing from traditional to holistic educational methods.…”
Section: The Challenges Of Holistic Educationmentioning
confidence: 98%
See 2 more Smart Citations
“…Holistic education is based on experiential learning methods, and students are defined as active participants in the educational process, building their knowledge through experience [4,9,13,[55][56][57]. However, this study found that students have difficulty changing from traditional to holistic educational methods.…”
Section: The Challenges Of Holistic Educationmentioning
confidence: 98%
“…Holistic education encompasses the development of the whole child-intellectually, emotionally, physically, socially, aesthetically, and spiritually-and promotes harmonious relationships with nature and people [9,10,55,56]. Various standardised tests easily measure a person's cognitive abilities, but we cannot measure a person's emotional intelligence, values, spirituality, and social skills.…”
Section: The Challenges Of Holistic Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a lifelong process and it applies to all students whatever their situation, course or mode of study -It is complex and involves a number of areas that interlink -It is about supporting students to develop a range of knowledge, skills, behaviours, attributes and attitudes which will enable them to be successful not just in employment but in life -It is a university-wide responsibility -It is about making the components of employability explicit to students to support their lifelong learning And what employability is not: Furthermore, employability, as mentioned earlier, has to be necessarily seen as a holistic process and not simplistically as a record of employment since this is only in fact a single piece of the employability jigsaw. Here, by holistic we mean fluid conversations and collaborations with all stakeholders (Sampath, 2015). There are indeed institutions who addressed and implemented employability skills in their curricula long before the Bologna process, but there are also programmes of study where learners are still oblivious to what professional translation practice entails, perhaps due to the lack of strong links with industry.…”
mentioning
confidence: 99%